Behavioral factors influencing usage of rural library services among youth in Malaysia - Abdullah, Farah Adila; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Institut Penyelidikan Pembangunan Belia Malaysia, 2013)
The main objective of this study is to explore the behavioral factors that impinge usage of rural library services among youth in Malaysia. This study employed a quantitative method, and a via multi-stage simple random sampling, a total of 400 rural library users among youth from four states in Peninsular Malaysia namely Kedah, Terengganu, Perak and Johor were chosen as the respondents. The data gained denote that all of the behavioral factors considered, namely perceived ease of use, perceived usefulness, attitude and social environment have positive and significant relationships with rural library usage among youths. It is highly recommended that the services offered in the rural library are in line with the youth needs and interests. This recommendation should be included in any rural library development plan as it will assist the concerned parties in constructing the best strategies by which to attract more people, particularly the younger generation, to use the services offered to them in rural libraries.